2011
DOI: 10.1074/jbc.m110.187815
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Protein Kinase A Anchoring Proteins Direct Prostaglandin E2 Modulation of Toll-like Receptor Signaling in Alveolar Macrophages

Abstract: Toll-like receptors (TLRs) direct a proinflammatory program in macrophages. One mediator whose generation is induced by TLR ligation is prostaglandin E 2 (PGE 2 ), which is well known to increase intracellular cAMP upon G protein-coupled receptor ligation. How PGE 2 /cAMP shapes the nascent TLR response and the mechanisms by which it acts remain poorly understood. Here we explored PGE 2 /cAMP regulation of NO production in primary rat alveolar macrophages stimulated with the TLR4 ligand LPS. Endogenous PGE 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 43 publications
2
67
0
4
Order By: Relevance
“…We have previously shown that PGE 2 , also via a EP2-cAMP-PKA axis, can modulate cytokine production initiated by TLR4 ligation when added to AMs at the same time as LPS (16). This effect involves PKA regulation of TLR4 signaling pathway components that culminate in the activation of NF-kB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that PGE 2 , also via a EP2-cAMP-PKA axis, can modulate cytokine production initiated by TLR4 ligation when added to AMs at the same time as LPS (16). This effect involves PKA regulation of TLR4 signaling pathway components that culminate in the activation of NF-kB.…”
Section: Discussionmentioning
confidence: 99%
“…The capacities of LTB 4 and PGE 2 to differentially influence macrophage functions have been linked to their abilities to ligate cognate G protein-coupled receptors (GPCRs) with resulting decreases and increases, respectively, in intracellular levels of the second messenger cAMP (13)(14)(15). We have previously shown that, through such increases in cAMP, PGE 2 can profoundly and rapidly suppress TLR4 pathway output by inhibiting downstream signaling events (16). However, whether PGE 2 and cAMP pathways can also influence the expression of TLR4 is not known.…”
mentioning
confidence: 99%
“…Western blotting was performed as previously described (83). Membranes were incubated with the following primary antibodies: STAT3 (1:1,000; #9139, clone 124H6), phospho-STAT3 (Tyr705; 1:250; #9145, clone D3A7), STAT1 (#9172), phospho-STAT1 (Tyr701; 1:500; #9167, clone 58D6), HIF-1α (1:1,000; #14179, clone D2U3T), and HK1 (1:1,000; #2024, clone C35C4) (all from Cell Signaling Technology) or β-actin (1:20,000; # A5441, clone UC15, Sigma-Aldrich), and then washed and incubated with appropriate fluorophore-conjugated secondary antibodies (1:2,000, anti-rabbit IgG, HRPlinked antibody, #7074, from Cell Signaling Technology).…”
Section: Equationmentioning
confidence: 99%
“…Several studies have shown that agents that elevate cAMP can enhance IL-10 transcription (19)(20)(21)(22)(23)(24). One example of this is the PG PGE 2 .…”
mentioning
confidence: 99%